Design and Analysis of Helical Cone Coil Heat Exchanger for Low Grade Heat Recovery - Ajay Hundiwale; Lokpriya Gaikwad; Sandeep Joshi (Journal of Heat and Mass Transfer Research)
The recovery of low-grade heat is crucial for energy conservation, particularly in manufacturing and process industries that discharge substantial waste energy into the atmosphere. This waste heat, varying from slightly above room temperature to several hundred degrees Celsius, can exist as liquids, gases, or a combination of both. Low-grade heat recovery, also known as waste heat recovery, involves capturing and transferring this energy using gas or liquid mediums, reintroducing it into the process as an additional energy source. This process is essential for improving energy efficiency and promoting sustainability, employing various techniques tailored to the waste heat temperature. Helical cone coils offer significantly enhanced heat transfer characteristics compared to straight tubes. These coils feature a secondary fluid flow running in planes parallel to the primary flow within their helical structure. This study focuses on designing and analyzing a shell and helical cone coil heat exchanger, highlighting its ability to reduce unit size compared to a standard shell-and-tube heat exchanger operating under the same thermal load. The experimental setup included a shell and helical cone coil configuration, utilizing diesel engine exhaust as the hot gas source and tap water as the cold fluid in a counterflow arrangement. The investigation revealed that helical cone coils extracted 15 to 20% more heat compared to conventional straight tubes, demonstrating improved effectiveness and compactness.